2021
DOI: 10.3389/fmicb.2021.715220
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile Single Cell Swimming Strategy: A Novel Motility Pattern Regulated by Viscoelastic Properties of the Environment

Abstract: Flagellar motility is important for the pathogenesis of many intestinal pathogens, allowing bacteria to move to their preferred ecological niche. Clostridioides difficile is currently the major cause for bacterial health care-associated intestinal infections in the western world. Most clinical strains produce peritrichous flagella and are motile in soft-agar. However, little knowledge exists on the C. difficile swimming behaviour and its regulation at the level of individual cells. We report here on the swimmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Chemical gradients are sensed by chemoreceptors, which trigger the autophosphorylation of the cytoplasmic CheA, which forms a complex with the receptor through the coupling protein CheW [ 33 , 41 ]. In response to these changes, CheA transfers its phosphate group to CheY, a diffusible cytoplasmic response regulator that interacts with the flagellar motor and leads to a modulation of motility characteristics [ 33 , 41 ]. This signalling core is highly conserved among all chemotaxis pathways [ 42 ].…”
Section: Types Of Bacterial Movementmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical gradients are sensed by chemoreceptors, which trigger the autophosphorylation of the cytoplasmic CheA, which forms a complex with the receptor through the coupling protein CheW [ 33 , 41 ]. In response to these changes, CheA transfers its phosphate group to CheY, a diffusible cytoplasmic response regulator that interacts with the flagellar motor and leads to a modulation of motility characteristics [ 33 , 41 ]. This signalling core is highly conserved among all chemotaxis pathways [ 42 ].…”
Section: Types Of Bacterial Movementmentioning
confidence: 99%
“…Although only a fraction of bacteria associated with animal hosts are motile, flagellar motility and chemotaxis are important for the successful colonisation and virulence of many pathogens, for example, gastrointestinal Campylobacter jejuni , Salmonella enterica serovar Typhimurium, Helicobacter pylori , and Vibrio cholerae [ 41 ]. In several cases, it has also been shown that the same flagellin, the protein subunit comprising the bacterial flagellum, can be a major driver of inflammation [ 35 ].…”
Section: Types Of Bacterial Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently investigated single cell motility and swimming behavior of C. difficile with the aid of a bacterial tracking program (YSMR), which generates quantitative data on motility parameter such as speed, turning points and run lengths, simultaneously from several hundred bacteria ( Schwanbeck et al, 2020 ). We could demonstrate that every motile C. difficile clade requires specific visco-elastic properties of the medium in order to display flagellar driven swimming motility ( Schwanbeck et al, 2021 ). A motility pattern with long run phases only occurred when the matrix elasticity was increased by high molecular weight molecules, as for example, polyvinylpyrrolidones (PVP) or mucins.…”
Section: Introductionmentioning
confidence: 99%
“…A motility pattern with long run phases only occurred when the matrix elasticity was increased by high molecular weight molecules, as for example, polyvinylpyrrolidones (PVP) or mucins. The motility behavior of C. difficile appears thus to be well adapted to the mucin-rich mucosal layer of the gastrointestinal tract ( Schwanbeck et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%